Ergonomics For People With Disabilities : Design For Accessibility - Aleksandra Polak-Sopinska; Jan Królikowski (Sciendo, 2018)
The world of developed economies looks at the problems of people with disabilities from a technical, social, psychological and informational perspective. Impacts in favour of people with disabilities are most often equated with the removal of barriers and integration. Nowadays, virtually every form of social and economic life should take in account inclusion and removal of barriers. Urban planning, the design of buildings, communication networks and the products, tools can be done from the perspective of removing barriers for people with disabilities. It is crucial to promote a way of thinking aimed at taking into account the needs of people with disabilities in the creation of all new civilizational solutions. Monograph “Ergonomics for People with Disabilities: Design for Accessibility” presents interdisciplinary attitude to the issue of designing for people with disabilities. The aim of the monograph is to present the factors affecting life activation of people with disabilities (including “50+” and “mature” people) and the problems that people with disabilities face by the participation in social and professional life and the daily activities and how design for accessibility can help with solving those problems. Concepts presented in the first part are focused on designing of products supporting inclusion such as wheelchairs, orthopaedic seats, carrier vests and hand tools. This part consist of five chapters. Field of interest of second part of the monograph is how to design accessible socio-technical environment. The subject is presented in four chapters on two hospital case studies, backyard sensorimotor path case and integrated therapeutic environment case. Third part is focused on universal design with ICT solutions. It consist of the concepts and analysis of solutions supporting people with disabilities and elderly people presented in six chapters. Scope of the last part is human factor design for barriers reduction. In three chapters problems such deafness, dementia and professional activity of people with disabilities were presented. Monograph includes the wide perspective of engineers, designers, architects, psychologists, sociologists, vocational counsellors and medicals that can inspire to new look at design for accessibility. Book Title: Ergonomics For People With Disabilities Book Subtitle: Design For Accessibility Scientific editors: Aleksandra Polak-Sopinska, Jan Królikowski Technical editor: Magdalena Wróbel-Lachowska Editors affiliations: Faculty of Management and Production Engineering, Lodz University of Technology, Poland Series Title: Advences in Production Management and Ergonomics Series ISSN: 2544-7610 Series Volume: 1e-ISBN: 978-3-11-061783-2 Edition Number: 1 Copyright: 2018 Publisher: De Gruyter Copyright Holder: Department of Production Management and Logistics, Faculty of Management and Production Engineering, Lodz University of Technology, Poland Number of Pages: 238 Department of Production Management and Logistics, Lodz University of Technology, Poland ABSTRACTING & INDEXING Ergonomics For People With Disabilities is covered by the following services: Baidu ScholarBayerische StaatsbibliothekBDSBoDBowker Book DataCiandoCNKI Scholar (China National Knowledge Infrastructure)DimensionsDOAB (Directory of Open Access Books)EBSCOElsevier – Scopus BooksExLibrisGoogle BooksGoogle ScholarNavigaReadCubeSemantic ScholarTDOne (TDNet)WorldCat (OCLC)X-MOLAdditionally, the proceedings volume is registered and indexed in the Crossref